229k views
5 votes
Simplify: cos2x-cos4 all over sin2x + sin 4x

Simplify: cos2x-cos4 all over sin2x + sin 4x-example-1
User Hans Vonn
by
5.6k points

1 Answer

7 votes

Answer:


(\cos\left(2x\right)-\cos\left(4x\right))/(\sin\left(2x\right)+\sin\left(4x\right))=\tan\left(x\right)

Explanation:


(\cos\left(2x\right)-\cos\left(4x\right))/(\sin\left(2x\right)+\sin\left(4x\right))

Apply formula:


\cos\left(A\right)-\cos\left(B\right)=-2\cdot\sin\left((A+B)/(2)\right)\cdot\sin\left((A-B)/(2)\right) and


\sin\left(A\right)+\sin\left(B\right)=2\cdot\sin\left((A+B)/(2)\right)\cdot\sin\left((A-B)/(2)\right)

We get:


=(-2\cdot\sin\left((2x+4x)/(2)\right)\cdot\sin\left((2x-4x)/(2)\right))/(2\cdot\sin\left((2x+4x)/(2)\right)\cdot\cos\left((2x-4x)/(2)\right))


=(-\sin\left((2x-4x)/(2)\right))/(\cos\left((2x-4x)/(2)\right))


=(-\sin\left((-2x)/(2)\right))/(\cos\left((-2x)/(2)\right))


=(-\sin\left(-x\right))/(\cos\left(-x\right))


=(-\cdot-\sin\left(x\right))/(\cos\left(x\right))


=(\sin\left(x\right))/(\cos\left(x\right))


=\tan\left(x\right)

Hence final answer is


(\cos\left(2x\right)-\cos\left(4x\right))/(\sin\left(2x\right)+\sin\left(4x\right))=\tan\left(x\right)

User Bojin Li
by
5.3k points